Health Care Costs of Alzheimer's and Related Dementias Within a Medicare Managed Care Provider. Issue 9 (September 2020) - Fishman, Paul A.; White, Lindsay; Ingraham, Bailey; Park, Sungchul; Larson, Eric B.; Crane, Paul; Coe, Norma B.
Abstract : Background: Although one third of Medicare beneficiaries are enrolled in Medicare Advantage (MA) plans, there is limited information about the cost of treating Alzheimer disease and related dementias (ADRD) in these settings. Objective: The objective of this study was to estimate direct health care costs attributable to ADRD among older adults within a large MA plan. Research Design: A retrospective cohort design was used to estimate direct total, outpatient, inpatient, ambulatory pharmacy, and nursing home costs for 3 years before and after an incident ADRD diagnosis for 927 individuals diagnosed with ADRD relative to a sex-matched and birth year-matched set of 2945 controls. Subject: Adults 65 years of age and older enrolled in the Kaiser Permanente Washington MA plan and the Adult Changes in Thought (ACT) Study, a prospective longitudinal cohort study of ADRD and brain aging. Measures: Data on monthly health service use obtained from health system electronic medical records for the period 1992–2012. Results: Total monthly health care costs for individuals with ADRD are statistically greater ( P <0.05) than controls beginning in the third month before diagnosis and remain significantly greater through the eighth month following diagnosis. Greater total health costs are driven by significantly ( P <0.05) greater nursing home costs among individuals diagnosed with ADRD beginning in the third month prediagnosis. Although total costs were no longer significantly greater at 8 months following diagnosis, nursing home costs remained higher for the people with dementia through the 3 years postdiagnosis we analyzed. Conclusion: Greater total health care costs among individuals with ADRD are primarily driven by nursing home costs.